Early Mobilization for Cardiovascular Function Recovery In Post-CABG Patients with Cardiopulmonary Bypass: A Systematic Literature Review - Siti Suryani Asmara; Yanuar Primanda (Indonesian Journal of Global Health Research, 2026)
Coronary artery bypass grafting (CABG) surgery is often performed with cardiopulmonary bypass (CPB) to maintain systemic perfusion during the procedure. While improving procedural safety, CPB can trigger a systemic inflammatory response and hemodynamic fluctuations that can potentially delay early recovery. Early mobilization is a crucial component of the postoperative recovery approach because it can prevent deconditioning, improve activity tolerance, and support cardiorespiratory stability. However, evidence regarding the form of early mobilization protocols and their impact on cardiovascular function recovery in post-CABG patients with CPB is scattered and heterogeneous. To synthesize scientific evidence regarding early mobilization in post-CABG patients with CPB. A systematic literature review was conducted following the PRISMA 2020 guidelines. A literature search was conducted in PubMed/MEDLINE, Scopus, and CINAHL databases for articles in English or Indonesian published between 2010 and 2025. A total of 518 articles were identified. After removal of duplicates, title and abstract screening, followed by full-text review, were performed. Eight studies with randomized controlled trial or quasi-experimental designs met the inclusion criteria and were analyzed using a narrative synthesis approach. The synthesis of these findings suggests that progressive early mobilization, including position changes, range-of-motion exercises, sitting, standing, and early ambulation, tends to provide better outcomes than conventional care or less structured mobilization. The most consistent positive impact is seen in increased functional capacity, particularly walking parameters such as the six-minute walk test prior to discharge. Several studies also report improved oxygenation and reduced pulmonary complications, decreased pain intensity, and some protocols, starting very early after extubation, are associated with shorter ICU and hospital stays. In addition to protocol factors, patient characteristics such as smoking status and self-efficacy-based educational support also influence recovery outcomes. Evidence from eight studies suggests that early mobilization after CABG with CPB is generally associated with better recovery outcomes, particularly in functional capacity, oxygenation, pulmonary complications, pain, and length of stay in some studies. These findings underscore the importance of implementing structured, progressive, and safety-based early mobilization, tailored to the patient's clinical condition, to optimize postoperative recovery.